If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + 23 = 16x + -1 Reorder the terms: 23 + 12x = 16x + -1 Reorder the terms: 23 + 12x = -1 + 16x Solving 23 + 12x = -1 + 16x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-16x' to each side of the equation. 23 + 12x + -16x = -1 + 16x + -16x Combine like terms: 12x + -16x = -4x 23 + -4x = -1 + 16x + -16x Combine like terms: 16x + -16x = 0 23 + -4x = -1 + 0 23 + -4x = -1 Add '-23' to each side of the equation. 23 + -23 + -4x = -1 + -23 Combine like terms: 23 + -23 = 0 0 + -4x = -1 + -23 -4x = -1 + -23 Combine like terms: -1 + -23 = -24 -4x = -24 Divide each side by '-4'. x = 6 Simplifying x = 6
| y=3(-1)-2 | | 6x+2=6x+10 | | 4x-9=23 | | y=3(-2)-2 | | 8x+9y=7 | | y=(1)+2 | | y=(-1)+2 | | y=(-2)+2 | | 5x-18=3x+10 | | 6n-4-3n=3n+10+4n | | x+35=3x+5 | | 7z+3=6+z | | y=2(-1)-1 | | y=2(-2)-1 | | X^4+14x^2+40=0 | | 4-2(5-x)=x-4(x-1) | | 4x-3=2x+6 | | 2x^2=4x-7 | | 6x^3-10x^2+45x-75=0 | | 25x^3+5x^2+10x+2=0 | | 10x^2+19x-15=0 | | 7x+3(x-6)=3(x+2)-5 | | 2x+3-7=4x-3 | | 0.9y-0.04y=6.5 | | -14=4k+2 | | -4x-5=-3x-9 | | 5d-1=9 | | 3(7x-3)-4(2x-10)=3(4x+5)-1 | | 2u^2+5u+2=(u+2)(u+2) | | 99-2x=34x+19 | | 12(3x+5)-6(2x-6)=4x-24 | | 2+5r=22 |